Matošʼs "Prolog" to the Milan Ogrizović’s and Andrija Milčinović’s Play "Prokletstvo" - Trojan, Ivan (Poznańskie Studia Slawistyczne, 2014)
On 7th May 1907, after publishing the play Prokletstvo in literary magazine „Savremenik”, the censorship approved performing the play in the Croatian national theatre in the theater season 1906/1907 under the condition that it would have passed through some radical changes. However, twenty days later all rehearsals were banned. Authors, Milan Ogrizović and Andrija Milčinović, show their brief union in resisting censorship publishing Prokletstvo into a separate book in year 1907 with Matosʼ Prologue that critically assails the institutions that stopped the play. Content and repercussions of Matosʼ editorial in Prokletstvo are the starting point of this article that outlines the cultural and political situation in Croatia in the first decade of the 20th century.